Azithromycin for treatment of hospitalised COVID-19 patients: a randomised, multicentre, open-label clinical trial (DAWn-AZITHRO). Issue 1 (28th February 2022) - Gyselinck, Iwein; Liesenborghs, Laurens; Belmans, Ann; Engelen, Matthias M.; Betrains, Albrecht; Van Thillo, Quentin; Nguyen, Pham Anh Hong; Goeminne, Pieter; Soenen, Ann-Catherine; De Maeyer, Nikolaas; Pilette, Charles; Papleux, Emmanuelle; et al.
Background and objectives: Azithromycin was rapidly adopted as a repurposed drug to treat coronavirus disease 2019 (COVID-19) early in the pandemic. We aimed to evaluate its efficacy in patients hospitalised for COVID-19. Methods: In a series of randomised, open-label, phase 2 proof-of-concept, multicentre clinical trials (Direct Antivirals Working against the novel coronavirus (DAWn)), several treatments were compared with standard of care. In 15 Belgian hospitals, patients hospitalised with moderate to severe COVID-19 were allocated 2:1 to receive standard of care plus azithromycin or standard of care alone. The primary outcome was time to live discharge or sustained clinical improvement, defined as a two-point improvement on the World Health Organization (WHO) ordinal scale sustained for at least 3 days. Results: Patients were included between April 22 and December 17, 2020. When 15-day follow-up data were available for 160 patients (56% of preset cohort), an interim analysis was performed at request of the independent Data Safety and Monitoring Board. Subsequently, DAWn-AZITHRO was stopped for futility. In total, 121 patients were allocated to the treatment arm and 64 patients to the standard-of-care arm. We found no effect of azithromycin on the primary outcome with a hazard ratio of 1.044 (95% CI 0.772–1.413; p=0.7798). None of the predefined subgroups showed significant interaction as covariates in the Fine–Gray regression analysis. No benefit of azithromycin was found on any of the short- and longer-term secondary outcomes. Conclusion: Time to clinical improvement is not influenced by azithromycin in patients hospitalised with moderate to severe COVID-19. Previous randomised controlled studies with azithromycin in hospitalised COVID-19 patients assessed end-points at fixed timepoints. Complementary to this, DAWn-AZITHRO assessed time to sustained improvement. No benefit of azithromycin was shown. https://bit.ly/3FapyC7